Geopolitical analysis of the Russo-American energy antagonism in the sub-system of the Balkans, in the greater system of the Mediterranean. - Ioannis Mazis (Civitas Gentium, 2017)
Greece has the ambiguous privilege of forming the intersection of two unstable Sub-systems of the Mediterranean Geopolitical Complex, i.e.: i. the Sub-system of the Balkans and ii. the Sub-system of Turkey and the Near East. We shall demonstrate that these two Sub-systems feature an intense joint function of instability in the present juncture and we shall also emphasize the main Geopolitical Factor that causes the aforementioned instability, i.e. energy security. Furthermore, we shall lay emphasis on the new Cold War-style antagonism between the two fundamental Poles of International Power, i.e. Moscow and Washington, an  antagonism  affecting  in  a  destabilizing  manner  the  Geopolitical  Complex  of  the  Mediterranean and in the Western Balkans regions as a main focal point. The term new Cold War-style is used so as to highlight the fact that there exists a considerable ideological distance between these two Poles (the same applies albeit in a different manner for the relations between Washington and Beijing), as was the case during the Cold War. The ideological difference in this case consists of the contrast between the neoliberal Western approach and the identitarian conservative approach of the East spearheaded by Moscow. Our analysis is based on the classic Anglo-Saxon geopolitical school and especially on N.J. Spykman’s «containment model», as the latter has been modified by Z. Brzesinsky. Our methodological approach is based on Systemic Geopolitical Analysis.